2019
DOI: 10.1016/j.hpb.2019.10.1498
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide survey on opinions and use of minimally invasive pancreatic resection

Abstract: Background: Distal pancreatectomy with celiac artery resection (DPCAR) is in use for borderline-resectable pancreatic cancer. It is believed that considerable reduction of the liver arterial supply after DPCAR may cause severe liver ischemia. Although the artery reconstruction is not a problem anymore the decision to reconstruct artery has to be justified. To study liver collateral arterial supply after temporary CHA, right gastroepiploic and accessory/ replaced left hepatic arteries (a/rLHA). Methods: Arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Finally, a lack of specific training was cited as the most common reason for not performing a minimally invasive approach [21]. These confirmed the findings of a pan-European survey during which, 45% of surgeons stated they had insufficient training in LDP [22], although 73% of surgeons had experience with minimally invasive distal pancreatectomy [22].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Finally, a lack of specific training was cited as the most common reason for not performing a minimally invasive approach [21]. These confirmed the findings of a pan-European survey during which, 45% of surgeons stated they had insufficient training in LDP [22], although 73% of surgeons had experience with minimally invasive distal pancreatectomy [22].…”
Section: Discussionsupporting
confidence: 68%
“…In various studies, it has demonstrated superiority over the open approach in terms of less blood loss, faster recovery, shorter hospital stays, and lower positive margin rate, with comparable morbidity and mortality [18], nodal assessment [19], overall survival, and lower total costs [20]. Unfortunately, LDP has not reached a uniform acceptance among HPB surgeons [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the multicentre randomized LEOPARD trial showed a 2‐day reduction in time to functional recovery and duration of hospital stay in favour of minimally invasive distal pancreatectomy compared with the open approach. Despite these positive results, the costs associated with minimally invasive surgery could be a barrier to further implementation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the necessity of formal robotic training programs in pancreatic surgery to ensure safe implementation. Additionally, these data are critically important to facilitate dissemination of the robotic approach, as pancreatic surgeons are eager to participate in formal training if the learning curve is surmountable 24 …”
Section: Discussionmentioning
confidence: 99%